Teaching entrepreneurship in senior design courses. - Goldberg, J. (IEEE Engineering in medicine and biology magazine)
A senior design capstone course can provide students with the opportunity to develop communication, interpersonal, and design skills and to learn about the product development process and project management. It is an excellent tool for preparing students for careers in biomedical engineering, especially those interested in employment with medical device companies. The author suggests that educators and design instructors should provide the opportunity for students to develop the skills and acquire the knowledge needed for successful careers in biomedical engineering. This includes development of (i) communication, interpersonal, teamwork, and design skills, (ii) an understanding of the legal, regulatory, and economic aspects of healthcare and the medical industry and (iii) basic business literacy. For additional in-depth entrepreneurial education, a graduate management degree with concentration in entrepreneurship might be the best approach. In order to develop an entrepreneurial perspective in all biomedical engineering students, "teachable moments" that are themselves in many of these courses should be taken advantage of.